Why we shouldn’t blame women for gender disparity in academia : perspectives of women in zoology - Slobodian, Veronica (2021)
The following letter, from a network of women zoologists, is a reply to the article of AlShebli et al. (2020), which suggests that female protégés reap more benefits when mentored by men and concludes that female mentors hinder the success of their female protégés and the quality of their impact. This contribution has two parts. First, we highlight the most relevant methodological flaws which, in our opinion, may have impacted the conclusions of AlShebli et al. (2020). Second, we discuss issues pertaining to women in science, bring a perspective of Women in Zoology and discuss how current diversity policies are positively changing our field.